2006
DOI: 10.1038/sj.ejcn.1602409
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol or stanol consumption does not affect erythrocyte osmotic fragility in patients on statin treatment

Abstract: Objective: To assess the effects of plant sterol or stanol ester consumption on their incorporation into erythrocytes and their effects on osmotic fragility of red blood cells. Design: Double-blind, randomized, placebo-controlled intervention trial. Subjects and intervention: Forty-one subjects on stable statin treatment -who already have increased serum plant sterol and stanol concentrations -first received for 4 weeks a control margarine. For the next 16 weeks, subjects were randomly assigned to one of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Indeed, in SPHR rats, which are characterized by increased plant sterol concentrations attributable to a defect in ABCG5, high plant sterol concentrations were associated with increased stroke risk, which was ascribed to a reduced erythrocyte deformability (32). However, in humans consuming plant sterolenriched margarines for 16 weeks, we could not confirm these effects despite an increase in red blood cell plant sterol content (33). In addition, Yang et al (34) have shown severe accumulation of plant sterols in adrenals of ABCG5/G8 2/2 mice, which led to depletion of cholesteryl esters.…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, in SPHR rats, which are characterized by increased plant sterol concentrations attributable to a defect in ABCG5, high plant sterol concentrations were associated with increased stroke risk, which was ascribed to a reduced erythrocyte deformability (32). However, in humans consuming plant sterolenriched margarines for 16 weeks, we could not confirm these effects despite an increase in red blood cell plant sterol content (33). In addition, Yang et al (34) have shown severe accumulation of plant sterols in adrenals of ABCG5/G8 2/2 mice, which led to depletion of cholesteryl esters.…”
Section: Discussioncontrasting
confidence: 53%
“…121 Furthermore, studies in humans and animal models showed that PS-enriched food consumption does not increase red cell fragility. [122][123][124][125][126][127] For example, in 1 study, 41 participants on stable statin treatment received a control margarine for 4 weeks and were randomly assigned to 1 of 3 possible interventions for the next 16 weeks (control margarine [n ¼ 11], plant sterol esterenriched margarine [n ¼ 15], plant stanol ester-enriched margarine [n ¼ 15]). 124 Daily plant sterol or stanol intake was 2.5 g. Campesterol levels in the red blood cells did not change.…”
Section: Effects Of Ps On Cellular Membranesmentioning
confidence: 99%
“…Osmotic fragility did not also change significantly in the plant sterol and plant stanol groups compared with the control group. 124…”
Section: Effects Of Ps On Cellular Membranesmentioning
confidence: 99%
“…In animals a decrease in the half life of erythrocytes and an increase in their fragility [50,51] have been observed. The implications of these animal studies for humans are unknown, although De Jong et al [52] did not observe any changes in the osmotic fragility of the erythrocyte membranes after phytosterol consumption. Furthermore, in the studies included in the meta-analysis by Moruisi et al [41] only minor digestive side effects were reported that were not confirmed in other studies [53].…”
Section: Introductionmentioning
confidence: 99%